The time-resolved atomic, molecular and optical science instrument at the Linac Coherent Light Source. Corrigendum - Peter Walter; Timur Osipov; Ming-Fu Lin; James Cryan; Taran Driver; Andrei Kamalov; Agostino Marinelli; Joe Robinson; Matthew H. Seaberg; Thomas J. A. Wolf; Jeff Aldrich; Nolan Brown; et al. (Journal of Synchrotron Radiation)
The name of an author in the article by Walter et al. (2022) [J. Synchrotron Rad. 29, 957–968] is corrected.